2021
DOI: 10.1177/15459683211029891
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Effects of Sequential 4-Channel Neuromuscular Electrical Stimulation for the Treatment of Acute, Subacute, and Chronic Dysphagia in a Prospective, Double-Blinded Randomized Clinical Trial

Abstract: Background. The precise mechanism of 2-channel neuromuscular electrical stimulation (NMES) treatment is unknown, and controversy remains over its efficacy. The sequential 4-channel NMES was newly developed based on normal contractile sequences of swallowing-related muscles. Objective. To assess the clinical efficacy of sequential 4-channel NMES during swallowing. Methods. In this prospective RCT, 52 inpatients with dysphagia (acute, subacute, and chronic state) after stroke, brain tumor, or encephalitis were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In our previous structured studies, the sequential 4-channel NMES showed significant compensatory effects in clinical and kinematic parameters during swallowing 12 . Moreover, in a recent randomized controlled study comparing rehabilitative effects of the sequential 4-channel NMES to the 2-channel NMES, the 4-channel NMES showed significant clinical improvement in penetration-aspiration scale and videofluoroscopic dysphagia scale scores.…”
Section: Introductionmentioning
confidence: 79%
“…In our previous structured studies, the sequential 4-channel NMES showed significant compensatory effects in clinical and kinematic parameters during swallowing 12 . Moreover, in a recent randomized controlled study comparing rehabilitative effects of the sequential 4-channel NMES to the 2-channel NMES, the 4-channel NMES showed significant clinical improvement in penetration-aspiration scale and videofluoroscopic dysphagia scale scores.…”
Section: Introductionmentioning
confidence: 79%
“…Given that No negative consequences were seen during the study, 4-channel NMES appears to hold the position of secure and well-absorbed dysphagia treatment option. Thus, a novel therapeutic approach for the method of compensation in dysphagic patients is consecutive 4-channel NMES 45) .…”
Section: Discussionmentioning
confidence: 99%
“…Optimal electrode placement for TNMES should target suprahyoid muscles or both suprahyoid and thyrohyoid muscles (Doan et al, 2022). Sequential fourchannel TNMES targeting suprahyoid, thyrohyoid, and other infrahyoid muscles has also shown significant clinical improvement in dysphagia treatment in terms of the videofluoroscopic dysphagia scale, penetration-aspiration scale (PAS), and kinematic analysis, highlighting the potential of this novel functional electrical stimulation system (Lee et al, 2021).…”
Section: Discussionmentioning
confidence: 99%